Conformity to feminine norms and self-objectification in self-identified feminist and non-feminist women. (March 2019) - Siegel, Jaclyn A.; Calogero, Rachel M.
Highlights: Feminine norms have been linked to self-objectification in women. Feminist self-identification is a potential buffer against self-objectification. No differences in self-objectification between feminist and non-feminist women. Beauty and romance-based norms accounted for unique variance in self-objectification. Feminist women endorsed sexual, romance, and domesticity norms less strongly. Abstract: This study investigated the association between the endorsement of feminine gender role norms and self-objectifying beliefs and behaviors in self-identified feminist and non-feminist women. One hundred and ninety-seven predominantly White heterosexual cisgender women attending a large university in southwestern Canada completed the study questionnaires for course credit. A one-way ANOVA demonstrated no differences in self-objectification between self-identified feminist and non-feminist women. Compared to non-feminist women, however, feminist women were less likely to endorse feminine norms for sexual fidelity, romantic relationships, and domesticity. Regression analyses indicated more endorsement of thinness, investment in appearance, and romantic relationships and less endorsement of domesticity accounted for unique variance in self-objectification. Overall, this study provides further evidence for the association between endorsement of feminine norms, especially the norms for beauty and romance, and the adoption of an objectified self-view, even among feminist women.